The legacy of the Tubingen school the relevance of nineteenth century theology for the twenty-first century - Dietrich, Donald J.; Himes, Michael J. (New York, NY Crossroad, 1997)
Includes bibliographical references.
Keywords: Tubingen School (Catholic theology)